Monitoring the Content of Polycyclic Aromatic Hydrocarbons in Soils and Natural Herbal Vegetation of Technogeneously Polluted Territory - Barbashev A.; Sushkova S.; Dudnikova T.; Minkina T.; Popov V. (Russian Journal of Earth Sciences, 2023)
Currently, one of the most important problems is the pollution of natural systems by polycyclic aromatic hydrocarbons (PAHs) as a result of human industrial activity. In this connection, it is necessary to carry out monitoring of territories subjected to the anthropogenic impact. As a result of the monitoring study of the impact zone of the fuel and energy complex enterprises, it was found that polycyclic aromatic hydrocarbons (PAHs) in the soil of the impact zone accumulate mainly up to 2 km along the line of the prevailing wind rose from the enterprise. The group composition of PAHs is dominated by 4-ring compounds, exceeding the background values by 23 times. At the same time, plants growing on the territory of the impact zone mainly accumulate such compounds as fluoranthene, pyrene, benzo[a]anthracene and phenanthrene, which is 70–82% of the total content of polyarenes in various parts of plants.